Energy spectrum of transition metal impurity in a semiconductor with an ideal surface - Melnychuk, S.V.; Yurijchuk, I.M. (Condensed Matter Physics, 1999)
Energy spectrum of the transition metal impurity which substitutes a cation
in a zink-blende structure semiconductor with an ideal surface is investigated theoretically. Model Hamiltonian of the semiconductor is treated
by the semi-empirical tight-binding method, and energy of deep 3d-levels
is determined by the Green function method within the framework of the
Kikoin-Flerov model. Numerical calculations are performed for Cr impurity
atoms in a CdTe semiconductor with an [100] ideal surface. It is shown
that in the case when the impurity substitutes an atom near the surface,
essential reconstruction of its energy spectrum takes place. One-electron
t₂ - and e -levels occurring from 3d -volume states for the crystal with an
ideal surface due to the lowering of the system symmetry split up. The
magnitude of the splitting is rather small, when impurity is situated near but
at some distance from the surface, and strongly increases when impurity
substitutes an atom directly on an ideal surface. Main mechanisms of one-electron deep level formation in the forbidden gap of a semiconductor with
ideal anion and cation surfaces are determined. Теоретично досліджується енергетичний спектр домішки з незаповненою 3d -оболонкою, що заміщує катіон в напівпровіднику з структурою цинкової обманки у випадку наявності в кристалі ідеальної поверхні. Модельний гамільтоніан напівпровідника будувався в моделі
напівемпіричного сильного зв’язку, а енергії глибоких 3d -рівнів визначалися методом функцій Гріна в рамках моделі Кікоєна-Флерова.
Числові розрахунки виконані для домішки Cr в напівпровіднику CdTe
з ідеальною поверхнею [100]. Показано, що у випадку розташування
домішки поблизу поверхні відбувається суттєва перебудова її енергетичного спектру. Одноелектронні t₂- i e -рiвнi, що обумовленi 3d -
центрами в об’ємному напiвпровiднику для системи, обмеженої iдеальною поверхнею, внаслiдок пониження симетрiї розщеплюються.
Величина розщеплення різко зростає для домішки, розташованої
безпосередньо на атомнiй площинi, що утворює ідеальну поверхню.
Внаслідок полярності поверхні [100] напівпровідника CdTe можливе iснування двох типiв поверхнi, якi по рiзному впливають на енергетичний спектр 3d -домiшок. Встановлено основні механiзми формування одноелектронних глибоких рiвнiв в забороненiй зонi напiвпровiдника для двох типів поверхнi.